Cardiovascular Changes in Kidney Diseases - M. B., Normatov; Kh. Kh., Gaffarov; M. S., Bekmuradova; F. Yu., Nazarov (American Journal of Biology and Natural Sciences, 2024)
Chronic kidney disease (CKD) poses a global health challenge, significantly increasing the risk of cardiovascular disease (CVD), which is the leading cause of mortality among CKD patients. Despite extensive research, there is limited understanding of how CKD impacts cardiovascular health in regions outside Western countries. This study addresses this gap by examining cardiovascular changes in CKD patients within Uzbekistan. Utilizing a cross-sectional design, we assessed 200 adult patients across various CKD stages, collecting data through clinical evaluations and standardized questionnaires. Our findings reveal a marked increase in cardiovascular complications with advancing CKD stages, including higher prevalence of hypertension, left ventricular hypertrophy, and atherosclerosis. The study highlights a progressive deterioration in cardiovascular health correlating with CKD severity, emphasizing the need for early detection and integrated care strategies. These results underline the necessity for targeted interventions to manage cardiovascular risk in CKD patients, particularly in underrepresented regions. Future research should explore longitudinal effects and the efficacy of specific treatments, as well as investigate the influence of regional factors on CKD-related cardiovascular complications. This study contributes valuable insights into CKD and CVD relationships, informing healthcare practices and policy development aimed at improving patient outcomes globally.